Resurgence of influenza and respiratory syncytial virus in Egypt following two years of decline during the COVID-19 pandemic: outpatient clinic survey of infants and children, October 2022 - Kandeel, Amr; Fahim, Manal; Deghedy, Ola; Roshdy, Wael H.; Khalifa, Mohamed K.; Shesheny, Rabeh El; Kandeil, Ahmed; Naguib, Amel; Afifi, Salma; Mohsen, Amira; Abdelghaffar, Khaled (BMC public health, 2023)
Two years after unprecedented low rates of circulation of most common respiratory viruses (SARS-CoV-2), the Egyptian ARI surveillance system detected an increase in acute respiratory infections (ARIs) with a reduced circulation of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), especially among school children. A national survey was conducted to estimate the burden and identify the viral causes of ARIs among children < 16 years of age. A one-day survey was carried out in 98 governmental outpatient clinics distributed all over Egypt 26 governorates. The four largest referral hospitals in each governorate where most influenza-like illness (ILI) patients seek care were selected. Using the WHO case definition, the first five patients < 16 years of age with ILI symptoms visiting the selected outpatient clinics on the survey day were enrolled. Basic demographic and clinical data of patients were collected using a linelist. Patients were swabbed and tested for SARS-CoV-2, influenza, and Respiratory Syncytial virus (RSV) by RT-PCR at the Central Laboratory in Cairo. Overall, 530 patients enrolled, their mean age was 5.8 ± 4.2, 57.1% were males, and 70.2% reside in rural or semi-rural areas. Of all patients, 134 (25.3%) had influenza, 111 (20.9%) RSV, and 14 (2.8%) coinfections. Influenza-positive children were older compared to RSV, (7.2 ± 4.1, 4.3 ± 4.1, p < 0.001), with more than half of them (53.0%) being school students. Dyspnea was reported in RSV more than in influenza (62.2% vs. 49.3%, p < 0.05). Among RSV patients, children < 2 years had a higher rate of dyspnea than others (86.7% vs. 53.1%, < 0.001). A resurgence of influenza and RSV was detected in Egypt in the 2022-2023 winter season. Influenza caused a higher rate of infection than RSV, while RSV caused more severe symptoms than influenza. Monitoring a broader range of respiratory pathogens is recommended to estimate the ARI burden and risky groups for severe disease in Egypt.